Lossless Text Compression Technique with LSB Technique to Hide Secret Message inside an Image (CLSB) - Dagez, Hanan Ettaher (International Journal of Intelligent Systems and Applications in Engineering, 2015)
Abstractâ This paper presents CLSB algorithm to improve and increase the security ofhiding message inside an image by using Least Significant Bit (LSB) method. This research attempts to improve the way has been introduced in [1], where they use digital images to hide Secret Text files. This method is working by distributing data (BMP image format) randomly without use any table to store the path of hiding data. CLSB propose new method to reduce size of dictionary index. Therefore, the main objective of this research is to develop a new method to increase the security by adding a secret key to decode and improve the quality by using LZW method to reduce the size of text file before hiding. Results proved and has also presented in this paper.Â  Â Abstractâ This paper presents CLSB algorithm to improve and increase the security ofhiding message inside an image by using Least Significant Bit (LSB) method. This research attempts to improve the way has been introduced in [1], where they use digital images to hide Secret Text files. This method is working by distributing data (BMP image format) randomly without use any table to store the path of hiding data. CLSB propose new method to reduce size of dictionary index. Therefore, the main objective of this research is to develop a new method to increase the security by adding a secret key to decode and improve the quality by using LZW method to reduce the size of text file before hiding. Results proved and has also presented in this paper.Â  Â